2007
DOI: 10.1021/ef060536r
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inorganic Matter on Trace Element Behavior during Combustion of Coal−Sewage Sludge Blends

Abstract: The effect of inorganic matter on the volatility of hazardous elements As, Be, Cd, Co, Cr, Cu, Hg, Mn, Ni, Pb, Sb, Se, Tl, and V during coal−sewage sludge combustion was studied. For this purpose, two bituminous coals from the Asturian Central Basin and sewage sludge treated with FeCl3 and lime were used. The combustion of sludge−coal blends was performed in a laboratory furnace at 800, 900, 1000, and 1100 °C. The results have shown that the inorganic matter of materials used in the sludge−coal blends affects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 20 publications
1
22
1
Order By: Relevance
“…Previous studies indicated that the combustion of sludge contained highly moisture had little effect on the reductionoxidation reactions of metal elements in bottom ash due to metal elements associated with Fe and Mn oxides (Chen and Yan 2012). Moreover, this would explain the relationship between water and kaolinite in soil, which might contribute to the capture of metals (especially Cu) during combustion (Folgueras et al 2007). Cu is mainly associated with iron (Fe) and clay minerals, which enhance the ionic strength of metal-clay sorption formation (Wei 1996).…”
Section: The Effect Of Moisture Content On Btex and Pah Emissionsmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies indicated that the combustion of sludge contained highly moisture had little effect on the reductionoxidation reactions of metal elements in bottom ash due to metal elements associated with Fe and Mn oxides (Chen and Yan 2012). Moreover, this would explain the relationship between water and kaolinite in soil, which might contribute to the capture of metals (especially Cu) during combustion (Folgueras et al 2007). Cu is mainly associated with iron (Fe) and clay minerals, which enhance the ionic strength of metal-clay sorption formation (Wei 1996).…”
Section: The Effect Of Moisture Content On Btex and Pah Emissionsmentioning
confidence: 98%
“…The plot of minerals indicates that a cluster of points around two-theta (2h) of 20°-70°. Minerals such as quartz (SiO 2 ), (Folgueras et al 2007;Tang et al 2013;Xu et al 2013). This result suggests that silicate and aluminosilicate frameworks are intact after combustion (Benson et al 1995).…”
Section: Ash Characterizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The elements Cr and Ni showed obviously higher retention in the bottom ash, 36% and 37% respectively, which means low volatility as reported by several researchers. Flogueras et al investigated the volatility of Cr and Ni during coal-sludge combustion in a laboratory electric furnace and found that Cr and Ni did not volatilize up to 1100°C (Folgueras et al, 2007). Zhang et al studied the distribution of heavy metals during the co-combustion of sewage sludge in a pulverized power plant and found that approximately 90% are transferred to bottom ash (Zhang et al, 2013).…”
Section: Heavy Metal Partitioning In Ashesmentioning
confidence: 99%
“…Improper sludge disposal can pose risks to both public health and the environment because most sludge contains heavy metals, disease-causing pathogens, organic and inorganic compounds. It is, therefore, of great significance to find a proper way to dispose wastewater treatment sludge to avoid secondary pollution [2][3][4][5]. Its handling methods and disposal techniques are a matter of great concern.…”
Section: Introductionmentioning
confidence: 99%